Analysis of DC Motor C42-L50 Using Linear Quadratic Regulator and Linear Quadratic Tracking for Community Empowerment Projects - Yulian Fatkur Rohman; Anggara Trisna Nugraha; Rama Arya Sobhita (Politeknik Perkapalan Negeri Surabaya, 2025)
This simulation represents a critical step in studying the waveform characteristics of the DC motor C42-L50 using a control system circuit with Linear Quadratic Regulator (LQR) and Linear Quadratic Tracking (LQT). Prior to initiating the simulation and data collection, a mathematical model was formulated using the datasheet of the DC motor C42-L50. Based on this model, further analysis was conducted, followed by simulations using MATLAB Simulink to explore and evaluate the differences between LQR and LQT in terms of the waveform or graphical characteristics of the DC motor. The analysis involved observing the simulation scope in MATLAB Simulink and experimenting with noise introduced into the system circuit. To align this study with community empowerment objectives, the findings aim to enhance the reliability and efficiency of DC motor applications in community service projects. For instance, the improved motor control facilitated by LQR and LQT methodologies can support the development of renewable energy solutions, agricultural automation systems, or other local technological advancements. This approach underscores the practical benefits of integrating advanced control systems into projects that promote sustainable community development.